PELAKSANAAN TAHFIDZ QUR’AN UNTUK MENINGKATKAN MINAT BELAJAR MEMBACA AL-QUR’AN DI MADRASAH ALIYAH MIFTAHUL ULUM KEDUNG PANJI - Sulis Setyowati (LP3M Sekolah Tinggi Agama Islam Ma'arif Magetan, 2022)
Among the causes of juvenile delinquency in young people is that they do not understand the contents of the Qur'an and lack of awareness of how important the Qur'an is as a guide to life in order to survive in the hereafter. This study uses qualitative research, the data obtained by using interviews, observation, and documentation. The analysis used is by using the concepts given by Miles & Huberman including: data reduction, data display and conclusion/verification. The results of this study indicate that 1) the reason for implementing the Qur'an tahfidz education program is because of the demands of the religious Kedung Panji community, to improve student achievement at the Miftahul Ulum Madrasah, to facilitate children to study in college with scholarships or to continue to Islamic boarding schools Qur'an. 2) The fasohah learning method uses the Ummi method which is now popular because it is easy to imitate and uses the Jibril method, namely the teacher reads first and the students imitate to memorize it using the Wahdah method and the Jama' method. 3) Implementation of the tahfidz Qur'an education program at MA Miftahul The implementation of the ulum begins with fashohah which is read by the teacher, the Fasohah uses the Jibril method and the ummi method, then students practice reading on their own according to recitation and the correct way of reading, then proceed with muroja'ah together. 4) implementation of the tahfidz Qur'an program increases students' interest in learning to read the Qur'an properly.